Pengaruh Kombinasi Fungi Mikoriza Arbuskula (FMA) dan Biochar Terhadap Hasil Tanaman Kedelai (Glycine max) Varietas Anjasmoro pada Tanah Salin - Muhammad Agus Mulyana; muharam; Asmanur Jannah (Faculty of Agriculture University of Singaperbangsa Karawang, 2022)
The experiment was conducted in Muara Baru Village, Cilamaya Wetan Distric, Karawang City. The objective of this experiment was to study get the best combination dosage of Mychorriza Arbuscular Fungus and Biochar on growth and yield of the soybean anjasmoro variety on the saline soil. The research used experimental method. It was arranged by randomized block design with 3 replications and 8 treatments. The treatments were : A (FMA 0 gram/plant, biochar 0 ton/ha), B (FMA 0 gram/plant, biochar25 ton/ha), C (FMA 0 gram/plant, biochar50 ton/ha), D (FMA 10 gram/plant, biochar 0 ton/ha), E (FMA 10 gram/plant, biochar25 ton/ha), F (FMA 10 gram/plant, biochar50 ton/ha), G (FMA 20 gram/plant, biochar 0 ton/ha), H (FMA 20 gram/plant, biochar25 ton/ha), I (FMA 10 gram/plant, biochar50 ton/ha). The data of each variable were analyzed using ANOVA and Duncan Multiple Range Test (DMRT) 5%. The biggest result according to weightof seedper plant is treatment Fwith doses 10g FMA/plant and 50 ton biochar/ha which the result : 17,25 g seed/ plant. Altough that treatment is not significan with D treatment with doses 10gFMA/plant and 0 ton biochar/plant which the result :16,20 g seed/plant.